Assessing Different Inoculum Treatments for Improved Production of Hydrogen through Dark Fermentation - Saleh Al-Haddad; Cynthia Kusin Okoro-Shekwaga; Louise Fletcher; Andrew Ross; Miller Alonso Camargo-Valero (Energies, 2023)
Hydrogen gas (H2) is an energy carrier that does not generate carbon dioxide emissions during combustion, but several processes in use for its production demand high energy inputs associated with fossil fuels and greenhouse emissions. Biological processes, such as dark fermentation (DF), have the potential to remove the dependency on fossil fuels in H2 production. DF is a process that encourages fermentative bacteria to ferment organic substrates to produce H2 as a truly clean energy carrier, but its success depends on removing the presence of competing H2−consuming microorganisms in the inoculum consortia. This paper addresses a strategy to enhance H2 production from different types of substrates by testing inoculum pre-treatment processes to inactivate H2−consuming bacteria, including acid-shock (pH 3), basic-shock (pH 10) and heat-shock (115 °C) methods. Digestate from anaerobic digesters processing sewage sludge was used to produce pre-treated inocula, which were subsequently tested in a batch bio-H2 potential (BHP) test using glucose as a substrate. The results show that heat-shock pre-treatment was the best method, reporting a H2 yield of 191.8 mL-H2/gVS added (the untreated inoculum reported 170.91 mL-H2/gVS added). Glucose conversion data show a high concentration of butyric acid in both treated and untreated inocula during BHP tests, which indicate that the butyrate pathway for H2 production was dominant; shifting this to the formate route could further enhance net H2 production. A standardised inoculum-conditioning method can help to consistently assess the biohydrogen potential of suitable feedstock for DF and maximise H2 yields.